WHITE SUPREMACY TOWARDS IGBO PEOPLE IN CHINUA ACHEBE’S THINGS FALL APART - AMALIA, FITRAH (Jurnal Ilmiah Mahasiswa FIB, 2013)
The phenomenon of colonization is important part in a history. Colonization iscontributed in the development of nations in the world. The concept of 3G (Gold,Gospel, and Glory) which becomes the background of European colonizers travelaround. Africa as a big continent which is rich with natural resources becomes thedestination of European colonizers. In fact, Africa cannot be separated with thecolonization issue and this is portrayed in literary works as the medium of the authorto react towards the social phenomena around them. One of the most influentialAfrican writers, Chinua Achebe, wrote his idea of British colonization in Nigeriaespecially Igbo land in his first novel, Things Fall Apart. He describes the Igbopeople and their custom before the arrival of the White people and what happenedduring and after the arrival of them in Igbo land.Postcolonial approach is applied in this study because Things Fall Apartdepicts the first contact of White colonizer and indigenous people. This approachleads to open the indication and the process of colonization. In line with colonization,the arising of White Supremacy is the main focus of this study to be analyzed. Tomeet the proper analysis and interpretation, this study uses White Supremacy theoryand other supporting theories such as negative stereotyping and race theory. Inaddition the retention of the Igbo people of White Supremacy which is happenedaround them is also investigated.This study uncovers the aspects which are supported the figuration of WhiteSupremacy. The result of this study also confirms that there are four aspects whichsupported the formation of White Supremacy. They are religion, law, institution andtechnology. Then, the negative stereotyping which is addressed to the Igbo createsdiscrimination by the White as their racism action. Whereas the Igbo retention isdivided into two ways, that are verbal and action. Key words: White Supremacy, Negative Stereotyping, Racism, Chinua Achebe, Retention, Things Fall Apart